Predictive role of the nighttime blood pressure - Hansen, Tine W; Li, Yan; Boggia, José; Thijs, Lutgarde; Richart, Tom; Staessen, Jan A (Hypertension (Dallas, Tex. 1979), 2011)
Numerous studies addressed the predictive value of the nighttime blood pressure (BP) as captured by ambulatory monitoring. However, arbitrary cutoff limits in dichotomized analyses of continuous variables, data dredging across selected subgroups, extrapolation of cross-sectional studies to prospective outcomes, and lack of comprehensive adjustments for confounders make interpretation of the literature difficult. We reviewed prospective studies with total mortality or a composite cardiovascular end point as an outcome in relation to the level and the circadian profile of systolic BP. We analyzed studies in hypertensive patients (n = 23 856) separately from those in individuals randomly recruited from populations (n = 9641). We pooled summary statistics and individual subject data, respectively. In both patients and populations, in analyses in which nighttime BP was additionally adjusted for daytime BP and vice versa, nighttime BP was a stronger predictor than daytime BP. With adjustment for the 24-hour BP, both the night-to-day BP ratio and dipping status remained significant predictors of outcome but added little prognostic value over and beyond the 24-hour BP level. In the absence of conclusive evidence proving that nondipping is a reversible risk factor, the option whether or not to restore the diurnal blood pressure profile to a normal pattern should be left to the clinical judgment of doctors and should be individualized for each patient. Current guidelines on the interpretation of ambulatory BP recording need to be updated.